INKLESS IMPRINTS: THE SHIFTING LANDSCAPE OF LITERATURE AND ECO-CONSCIOUS DIGITAL PUBLISHING - P, Padmapriya; Alagesan, M.; B., Ramya (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The Digital era has marked numerous developments in the fields of academics and technology. The fusion of technologies with academics has taken the academic forum to greater levels. In human history, the invention of paper played a significant role in communication and documenting knowledge. This research focuses on how the massive usage of paper is contributing to climate change and attempts to find to what magnitude the effective usage of digital publishing can be the solution to protect the environment. The production process of paper, from cutting down trees, to transportation, creates an accountable carbon footprint, water pollution, waste generation and so on. It is observed that approximately four million books are published in a year, creating the need for 400 million papers (approximately 40000 trees). Thus, this research focuses on digital Publishing, using literature on digital platforms and print-on-demand as remarkable phenomena that benefit academia and the environment.